2000
DOI: 10.1007/s005860050004
|View full text |Cite
|
Sign up to set email alerts
|

Early histologic changes in lower lumbar discs and facet joints and their correlation

Abstract: IntroductionThe precise etiology of low back pain is difficult to establish and remains unclear. It is believed, however, that degenerative changes in the spinal motion segment play an important role. These may occur in discs and associated facet joints, which are regarded as an interdependent functional spinal unit (FSU). Biomechanical studies clearly show the importance of the facet joints as a motion-restricting, as well as a stress-and load-sharing factor for the disc [1,9,13,19]. Therefore, it is conceiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 26 publications
1
63
0
3
Order By: Relevance
“…This was [4]. Another histological study from Gries et al [7] showed no correlation between early histological changes in lumbar disks and the associated facet joints (Fig. 8).…”
Section: Discussionmentioning
confidence: 85%
“…This was [4]. Another histological study from Gries et al [7] showed no correlation between early histological changes in lumbar disks and the associated facet joints (Fig. 8).…”
Section: Discussionmentioning
confidence: 85%
“…Another important cause of axial back pain is facet joint osteoarthritis, which consists in the decrease of the thickness and regularity of the cartilage layer of the facet joints, also called apophyseal or zygoapophysial joints. Disc degeneration and facet joint osteoarthritis are commonly observed together in the same patient and spinal level [20,26,35] and a possible correlation between these two pathologies is currently debated [62].…”
Section: Discogenic Painmentioning
confidence: 99%
“…Any imbalance might lead to impaired functional properties. From a histologic point of view, the occurrence of clefts and tears are the major hallmarks of disc degeneration, [5,6,7,9,10,11,15,18,36,40,41,42,43], but there is very little (almost no) evidence that invading cells might contribute to this process of matrix degradation. Therefore, it can be assumed that local cells are involved in any degradation process.…”
Section: Introductionmentioning
confidence: 99%